A History of dentistry in the Philippines - Robles, Gonzalo S. (Manila : Professionals Publishing Company Inc., 1982)
It has been said that the heritage of the past is the seed that brings forth the harvest of the future.
I. Introduction -- II. Dental legislation -- III. Board of dental examiners -- IV. Dentist licensure examination -- V. Dental education -- VI. The Dental profession -- VII. Dental research -- VIII. Public health dentistry -- IX. Dentists in the government service -- X. Dental affairs
Includes bibliographical references and index.
Keywords: DENTISTRY -- HISTORY; DENTISTRY -- HISTORY -- PHILIPPINES